Enhancing rice yield in acidic soil through liming and fertilizer management: Lime and fertilizer maximize rice yield in acid soil (Journal of the Bangladesh Agricultural University, 2018)
The effect of lime and fertilizer application, as the management of soil acidity, on the growth and yield of rice cv. BRRI dhan50 was investigated during Aman rice season at the Agronomy Field Laboratory of Sylhet Agricultural University, Bangladesh. The experiment was consisted of two factors namely lime and fertilizer. There were four levels of lime (0, 0.50, 1.00, and 1.50 t ha–1 of CaCO3.MgCO3) and three levels of fertilizers (control, FYM @ 10 t ha–1, and chemical fertilizer @ 100-30-42-4-3-0.4 kg ha–1 of N-P-K-Ca-S-Zn). The experiment was laid out in a randomized complete block design with three replications where the unit plot size was 4.0 m x 2.5 m. Growth parameters, yield components and yield of BRRIdhan 50 rice increased with increasing lime rate in association of fertilizer in acidic soil. The highest grain yield (2.90 t ha–1) was recorded from the application of 1.50 t ha–1 lime and the lowest (2.06 t ha–1) was from control (0t ha–1), irrespective of fertilizer. On the other hand, the best effect of fertilizers on grain yield (3.08 t ha–1) was found with the application of FYM @ 10 t ha–1 and the lowest yield (1.59 t ha–1) was in control. The treatment combination of lime 1.50 t ha–1 and FYM (@ 10 t ha–1 produced the highest grain yield (3.60 t ha–1), which was followed by treatment combination of lime 1.50 t ha–1 and chemical fertilizer @ 100-30-42-4-3-0.4 kg ha–1 of N-P-K-Ca-S-Zn (3.28 t ha–1). Additionally, application of lime and FYM improved the soil fertility and properties of acidic soil for crop production by increasing the pH, organic matter and availability of some essential nutrients. From the study, it was indicated that both FYM and lime could affect to enhance the grain yield of rice in acidic soil.J. Bangladesh Agril. Univ. 16(3): 357–365, December 2018